Hubungan Pola Asuh Orang Tua dengan Kedisiplinan Siswa Kelas Tinggi di Sekolah Dasar - sUNDARI sUNDARI; rukayah rukayah; sidrah afriani Rahman (Universtas Negeri Makassar, 2022)
The problem in this study is the lack of student discipline. Student discipline does not just arise, but there are parties who play a very important role in children's education, one of which is through parenting applied by parents. This research is a quantitative research with the type of correlational research which aims to determine the relationship between parenting patterns and high grade elementary school students' discipline. The results showed that obtained rx = 0.412 then the relationship between the two variables was classified at the level of relationship in the